2011
DOI: 10.1017/s0014479711000883
|View full text |Cite
|
Sign up to set email alerts
|

RESISTANCE TO DIEBACK DISEASE CAUSED BY FUSARIUM AND LASIODIPLODIA SPECIES IN CACAO (THEOBROMA CACAO L.) GENOTYPES

Abstract: Fusarium and Lasiodiplodia species invade feeding lesions caused by mirid bugs (Distantiella theobroma [Dist.] and Sahlbergella singularis Hagl.) and inflict serious damage and yield loss to susceptible cacao (Theobroma cacao L.) varieties in West Africa. As it is the fungal invasion rather than the physical feeding injury by mirids that cause dieback and tree death in cacao, a dieback resistance strategy in cacao crop must take into account resistance to these causal agents. Twenty-nine and 15 cacao genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
0
13
1
Order By: Relevance
“…All mirid active stages feed on cacao stems and pods causing little direct damage. However, their phytotoxic saliva results in sunken lesions that become infected secondarily by parasitic fungi that cause shoot die back (Johnson, 1962;Adu-Acheampong et al, 2012). Damage varies from mild 'blast' where leaves on fan branches die but remain hanging, through 'staghead' where the whole canopy of individual trees is defoliated and shoots die back, to the most severe 'pockets' where up to 100 trees become stagheaded with corresponding breaks in the cacao canopy (Williams, 1954;Johnson, 1962).…”
Section: Introductionmentioning
confidence: 99%
“…All mirid active stages feed on cacao stems and pods causing little direct damage. However, their phytotoxic saliva results in sunken lesions that become infected secondarily by parasitic fungi that cause shoot die back (Johnson, 1962;Adu-Acheampong et al, 2012). Damage varies from mild 'blast' where leaves on fan branches die but remain hanging, through 'staghead' where the whole canopy of individual trees is defoliated and shoots die back, to the most severe 'pockets' where up to 100 trees become stagheaded with corresponding breaks in the cacao canopy (Williams, 1954;Johnson, 1962).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors such as the length of the lesion in cambium, wilting and yellowing of the leaves can be used to determine the resistance of the cocoa genotypes to dieback. Adu Acheampong et al (2012) showed the existence of a direct correlation between visible symptoms of dieback and the lengths of necrosis in the cambium. Indeed, cocoa varieties with a large lesion length are more susceptible to dieback and those with a small length of lesion tolerant.…”
Section: A B C D Ementioning
confidence: 99%
“…Chemical and biological control methods were usually practiced in order to prevent the plant diseases and to protect the crop plants against pathogens. After more than a century experience of controlling dieback disease, the ideal control regime is still to be found (Adu-Acheampong et al, 2012). Implementation of integrated disease management (IDM) programs which combine cultural, chemical, and biological approaches are highly recommended to control crop diseases, reduce cost, and improve production efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…and Lasiodiplodia spp. (Adu-Acheampong et al, 2012Voula et al, 2018) that can lead to cocoa dieback (Anikwe et al, 2015). There is also mounting evidence that yield losses caused by mirid feeding are principally due to abortion of young fruits (Yede et al, 2012).…”
Section: Introductionmentioning
confidence: 99%